Strategy to Accelerate the Utilization of Tatanggo Terminal as a New Economic Growth Lever in Buru Regency - Jamaludin Samak; Maryam Sangadji; Izaac Tonny Matitaputty (LP2M IAIN Palopo, 2026)
Tatanggo Terminal in Buru Regency was built as a transportation hub and new economic growth center, but until 2025 it did not function as planned. This study aims to: (1) identify the factors causing the terminal's non-functioning, (2) analyze the potential of Tatanggo Terminal in supporting local economic growth, and (3) formulate strategies to accelerate terminal utilization. The study used a qualitative approach with a case study design through in-depth interviews, field observations, and document analysis. Data analysis was carried out using the Miles & Huberman model, followed by strategic analysis of SWOT, IFAS, EFAS, and the IE Matrix. The research results show that there are five main factors that cause Tatanggo Terminal to not function: (1) non-comprehensive planning, (2) weak institutions and enforcement of regulations, (3) lack of transportation route connectivity, (4) community socio-economic preferences for the Old Market, and (5) local political intervention. Nevertheless, the terminal has great potential as a distribution center for agriculture, horticulture, fisheries, and MSMEs along with the growth of public consumption, the increase in the number of vehicles, and the saturation of the Old Market's space capacity. The results of the SWOT.IFAS.EFAS analysis place Tatanggo Terminal in the